Illusions within an Illusion. (December 2015) - Deręgowski, Jan B.
Effect of perceptual inversion on illusion figures seen monocularly was explored using Ponzo and Muller-Lyer stimuli. It was found that inversion nullified the Ponzo effect but not the Muller-Lyer effect. This suggests that the determinants of the two illusory effects differ in their origin.